Copper-Catalyzed Direct α-Nitration of Nitrostilbenes with Nitrogen Dioxide - Chen, Kai Hao; Gao, Xi; Zou, Hui; Xiao, Guan Sheng; Peng, Xin Hua (Synlett, 2019)
A novel and efficient method for the direct α-nitration of nitrostilbenes was developed in which NO2 was used as the nitro source. This method provided (E)-α-nitrostilbenes derivatives in moderate to good yields. A broad substrate scope, mild and convenient conditions, and high stereoselectivity are important features of this method.
Keywords: stilbenes; nitration; nitrogen dioxide; nitroalkenes; ionic process